Evaluating the need for culturally sensitive communication training for doctors engaged in international medical tourism using the lens of communication accommodation theory - Tyagi, Himanshu; Mehra, Payal (International Journal Of Community Medicine And Public Health, 2025)
Background: The exponential growth of the international medical tourism industry, especially in countries like India, has necessitated the need for effective communication between healthcare providers and international patients. Culturally sensitive communication is crucial in this context, as it directly impacts patient satisfaction, compliance, and overall health outcomes. This study evaluates the need for culturally sensitive communication training for doctors engaged in international medical tourism through the framework of Communication Accommodation Theory (CAT). Methods: A cross-sectional study was conducted with 1,476 international patients at a leading healthcare institution in Delhi, India. Data were collected using a comprehensive questionnaire designed to capture cross-cultural communication nuances, focusing on both verbal and non-verbal communication. The study employed a post-positivist research approach, and data were analysed using SPSSv24, Smart PLS 3, and MGA-PLS to examine the relationships between communication styles, cultural sensitivity, and patient experiences. Results: The analysis revealed a strong positive relationship (path coefficient = 0.809) between patient expectation and patient experience, indicating that culturally competent communication significantly enhances patient outcomes. Additionally, patient expectations were found to mediate the relationship between outcome and patient experiences, emphasizing the importance of managing these expectations effectively. Conclusions: The findings underscore the critical need for culturally sensitive communication training for doctors involved in international medical tourism. By adopting communication strategies that accommodate the cultural preferences of international patients, healthcare providers can significantly improve patient satisfaction and outcomes, thereby enhancing the global competitiveness of medical tourism destinations like India.